SISTEM PENCARIAN DAN PEMESANAN RUMAH KOS - Pratikto, Harri Singgih; Suraya, Suraya; Sutanta, Edhy (Jurnal Script, 2014)
ABSTRACTEase of obtaining information rooming house is one of the demands in the city of Yogyakarta, especially for newcomers such as students and students who need a place to stay temporarily. Migrants who wish to settle temporarily in the city of Yogyakarta usually face obstacles such as not knowing the area, or do not have a friend who can demonstrate appropriate boarding house. On the other hand, the availability of information technology can help users in many kinds of needs, including as a means of access to information that can be done easier, faster, cheaper, and safer. This study develops an application of geographic information systems (GIS) for a web-based help migrants in the city of Yogyakarta in the process of finding and booking boarding houses according to their needs, and help homeowners boarding house boarding in marketing online. The application is developed by using CodeIgniter framework and Google maps.Â Keywords: CodeIgniter, Google maps, pencarian, rumah kos, sistem informasi geografis.Â